Electrochemistry of organometallic compounds. Part IV. Oxidations of benzylic derivatives and p-substituted benzylic derivatives of bis(dimethylglyoximato) and bis(salicylaldehyde)o-phenylenediimine cobalt(III) in dimethylformamide - Benedetti, A. V.; Dockal, E. R.; Chum, H. L.; Rabockai, T. (Elsevier, 1982)
The electrochemical oxidation of some p-substituted benzylic derivatives of Co(III) dimethylglyoximato and Co(III)bis(salicylaldehydc)o-phenylenediimine in dimethylformamide. 0.2 M in tetraethyammonium perchlorate, on a platinum electrode, at several temperatures, is described as an ECE type, the first electrochemical step being a quasi-reversible one-electron charge transfer at room temperature. At temperatures around -20°C, or lower, the influence of the irreversible chemical decomposition of the oxidized species, via a solvent or other nucleophilic-assisted reaction, is negligible. It is suggested that at low temperatures the oxidation to the formally CoIV-R species is followed by an isomerization reaction in which this complex is partially transformed in a CoIII-(R) species or a s π-complex which undergoes an electroreduction at less positive potentials than those corresponding to the reduction of the CoIV-R species. © 1982.